Physical activity of pregnant and postpartum women - Łosień, Tomasz; Mędrak, Anna; Plaskacz, Paweł; Bajerska, Izabela; Reut, Magdalena; Dragon, Emilia; Polko, Martyna; Cebula, Aleksandra (Journal of Education, Health and Sport, 2017)
Introduction: One of the basic elements of a healthy lifestyle is regular physical activity. Nowadays, more and more women during pregnancy take up the topic of the impact of physical activity and diet on the child developing in the womb. The existence of birth schools allows you to prepare for delivery, obtain information on acceptable safe activity adapted to the health of the future mother and ways of rational nutrition. The silhouette of women during pregnancyis constantly changing. Literature often shows the subject of a decrease in self-esteem during this period, associated with hormonal changes, appearance, fatigue and limitation of time for self-development. In the literature, we find two different positions of women about the subject of physical activity during pregnancy. The first position speaks of virtually complete limitation of activity, the second is about taking minimal activity such as before pregnancy. The aim of the study: 1) What impact on physical well-being in pregnant women and postpartum is having, 2) Is there a relationship between physical activity and pregnancy? 3) Is there a relationship between physical activity and postpartum period?, 4) What is the most common motivation to undertake physical activity after delivery? Material and methods:57 women aged 18 to 47 participated in the study. The study used an original anonymous survey of 28 questions. The questions concerned, among others: pregnancy, postnatal period, physical activity during pregnancy and after delivery. Conclusions: Taking physical activity during pregnancy and after childbirth influences the increase of self-esteem and well-being of women. About 25% of women surveyed did not return to physical activity a year after delivery. The basic factors influencing the activity after childbirth are the desire to improve the appearance, well-being and return to fitness which they presented before delivery.